Late- versus early-onset geriatric depression in a memory research center - Carol Dillon (Dove Medical Press, 2009)
Carol Dillon1, Ricardo F Allegri2, Cecilia M Serrano1, Mónica Iturry1, Pablo Salgado1, Frank B Glaser1, Fernando E Taragano21Memory Research Center, Department of Neurology, Hospital General Abel Zubizarreta, GCBA Buenos Aires, Argentina; 2Department of Neuropsychology (SIREN), CEMIC University, Buenos Aires, ArgentinaObjective: To contrast early-onset (<60 years) and late-onset (>60 years) depression in geriatric patients by evaluating differences in cognition, vascular comorbidity and sociological risk factors. Both patient groups were compared with normal subjects.Materials and methods: We recruited 76 patients with depressive symptoms (37 late onset and 39 early onset) and 17 normal controls matched by age and educational level. All subjects were assessed using a semistructured neuropsychiatric interview and an extensive neuropsychological battery. Vascular and sociological risk factors were also evaluated.Results: We found a significant variation in performance between depressive patients and normal controls in most cognitive functions, especially memory (P < 0.0001), semantic fluency (P < 0.0001), verbal fluency, and digit-symbol (P < 0.0001). Late-onset depression patients scored lower and exhibited more severe impairment in memory domains than early-onset depression patients (P < 0.05). Cholesterol levels and marital status were significantly (P < 0.05) different between the depressive groups. Both depressed groups (early- and lateonset) were more inactive than controls (P < 0.05; odds ratio: 6.02).Conclusion: Geriatric depression may be a manifestation of brain degeneration, and the initial symptom of a dementia. It is important to consider this in the treatment of patients that exhibit late-onset depressive symptoms.Keywords: early- and late-onset depression, geriatrics, cognition